PELATIHAN PENGENALAN E-COMMERCE BAGI PELAKU UMKM DI DESA BANDAR AJI KABUPATEN LAHAT - puspita, desi; Masdalipa, Risnaini; Asminah, Asminah (Universitas Multi Data Palembang, Fakultas Ilmu Komputer dan Rekayasa, 2023)
Bandar Aji hamlet is a hamlet that has banana chips and cassava chips which have the potential to be improved in marketing, but in reality marketing is only for certain groups so that the business carried out is not optimal and sometimes suffers considerable losses. The purpose of this study is to assist micro, small and medium enterprises (UMKM) in increasing the marketing of UMKM products in the Bandar Aji hamlet. This e-commerce software development was built using a prototype software development model. The development stage begins with communication, rapid planning, rapid design models, prototyping, submission and providing feedback on development. e-commerce is built using a website-based application, so that business actors can easily promote their business results. The main target for the use of e-commerce technology is UMKM in the Bandar Aji village. Users of this application are administrators who have full rights to application processing, UMKM are admins who have the right to enter product data, consumers who have the right to choose and order products. The results of trials and evaluations conducted on UMKM in Bandar Aji hamlet, showed that using e-commerce software could increase the marketing of UMKM products